Transnational work and workplace as infrastructure: Sino-British international branch campuses and academic mobilities. Issue 2 (4th March 2017) - Liu, Tianfeng; Lin, Weiqiang
Abstract: Transnational education is growing apace in recent years, with international branch campuses (IBCs) becoming an increasingly prominent feature in Asia's higher education landscape. This paper examines a Sino-British IBC in China as an inroad for illuminating the mobilities such set-ups entrain as a migration infrastructure tied to transnational work and workplace. Using Bourdieu's concepts of field, capital and habitus, we interrogate the processes of 'branch-making' in relations to the IBC in question, teasing out its strategies in recruitment, and, as part of its social and material environment, opposing circumstances that motivate the re-mobilisation of academic migrants. The paper argues for a need to consider not just interventions of the state or individuals' personal decisions in comprehending skilled migration, but also how the workplace possesses the power to shape movement and generate mobilities.